Alterations of redox and iron metabolism accompany the development of HIV latency. (11th March 2020) - Shytaj, Iart Luca; Lucic, Bojana; Forcato, Mattia; Penzo, Carlotta; Billingsley, James; Laketa, Vibor; Bosinger, Steven; Stanic, Mia; Gregoretti, Francesco; Antonelli, Laura; Oliva, Gennaro; Frese, Christian K; et al.
Abstract: HIV‐1 persists in a latent form during antiretroviral therapy, mainly in CD4 + T cells, thus hampering efforts for a cure. HIV‐1 infection is accompanied by metabolic alterations, such as oxidative stress, but the effect of cellular antioxidant responses on viral replication and latency is unknown. Here, we show that cells survive retroviral replication, both in vitro and in vivo in SIVmac‐infected macaques, by upregulating antioxidant pathways and the intertwined iron import pathway. These changes are associated with remodeling of promyelocytic leukemia protein nuclear bodies (PML NBs), an important constituent of nuclear architecture and a marker of HIV‐1 latency. We found that PML NBs are hyper‐SUMOylated and that PML protein is degraded via the ubiquitin–proteasome pathway in productively infected cells, before latency establishment and after reactivation. Conversely, normal numbers of PML NBs were restored upon transition to latency or by decreasing oxidative stress or iron content. Our results highlight antioxidant and iron import pathways as determinants of HIV‐1 latency and support their pharmacologic inhibition as tools to regulate PML stability and impair latency establishment. Synopsis: HIV‐1 infection leads to alterations in redox and iron metabolism of the host cell. Here, HIV‐1‐induced reshaping of cellular metabolism is shown to regulate HIV‐1 latency establishment and reactivation via regulation of PML nuclear body dynamics. HIV‐1 replication hijacks cellular metabolism by inducing oxidative stress and iron import. Redox and iron imbalance leads to degradation of the HIV‐1 latency marker PML via the ubiquitin/proteasome pathway. Upregulation of antioxidant responses facilitates cell survival and replenishment of PML, but can lead to HIV‐1 latency establishment. Latency reversal recapitulates the metabolic dysregulation induced during productive infection. Abstract : Activation of cellular oxidative stress responses and iron import upon HIV‐1 infection triggers latency establishment via remodeling of PML nuclear bodies.